THE INFLUENCE OF IT-ASSISTED RECIPROCAL TEACHING LEARNING MODEL AND INDEPENDENT LEARNING ON THE LEARNING OUTCOMES OF CLASS V STUDENTS AT SDN 101941 MELATI, PERBAUNGAN - Fadhillatu Jahra Sinaga; Deny Setiawan; Daulat Saragi (Sensei International Journal of Education and Linguistic, 2022)
This study aims to determine (1) the differences in student learning outcomes in PPKn who are taught using an IT-assisted reciprocal learning model using a reciprocal learning model without IT assistance; (2) PPKn learning outcomes of students who have high learning independence compared to students who have low learning independence; (3) The interaction between the learning model and learning independence on student PPKn learning outcomes. This research is in the form of a quasi-experimental design with a 2 x 2 factorial design. The population of this research is all fifth grade students at SDN 101941 Melati Perbaungan District, as many as 2 classes with a total of 50 students. The sample selection was taken by using a total sampling technique, namely from the two classes as a whole set as a sample. Thus, the sample was determined, namely class VA as group A and class VB as group B. Class determination for the application of the learning model was determined by group A consisting of 25 students for classes taught using the IT-assisted reciprocal teaching learning model, and group B consisting of of 25 students for classes taught using the reciprocal teaching learning model without IT media. The research instrument used a multiple-choice learning outcome test with 25 questions and a student learning independence instrument in the form of a questionnaire consisting of 20 items that were declared valid and reliable. Data analysis using two-way Anova. The results showed (1) there was a significant difference between the PPKn learning outcomes of students who were taught the IT-assisted reciprocal model compared to the IT-assisted reciprocal model; (2) PPKn learning outcomes of students who have high learning independence are higher than students who have low learning independence; (3) There is an interaction between the learning model and independent learning in influencing student PPKn learning outcomes